2016
DOI: 10.1002/1873-3468.12514
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor inhibitor of growth 4 binds double‐stranded DNA through its disordered central region

Abstract: The tumor suppressor inhibitor of growth 4 (ING4) regulates chromatin structure by recruiting the histone acetyl transferase complex HBO1 to sites with histone H3 trimethylated at K4. ING4 dimerizes through its N-terminal domain and recognizes H3K4me3 by the C-terminal plant homeodomain (PHD). The central region of ING4 is disordered and contains the nuclear localization signal. Here, utilizing electrophoresis and nuclear magnetic resonance, we show that ING4 binds double-stranded DNA through its central regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…As also pointed out by the authors , isoforms of ING4 lacking the PHD have been described and the biological activities of ING2 in promoting muscle differentiation appear to be independent of the PHD . This suggests that the interaction of the IDR/NLS of the INGs with DNA may impart biological functions to the ING family of proteins beyond their suspected role of strengthening nucleosome binding.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…As also pointed out by the authors , isoforms of ING4 lacking the PHD have been described and the biological activities of ING2 in promoting muscle differentiation appear to be independent of the PHD . This suggests that the interaction of the IDR/NLS of the INGs with DNA may impart biological functions to the ING family of proteins beyond their suspected role of strengthening nucleosome binding.…”
mentioning
confidence: 66%
“…Having previously shown that interacting amino termini of ING4 proteins promote formation of homodimers that are capable of targeting carboxyl ING4 PHDs to adjacent histones, the Blanco group has explored the function of the disordered central region of ING4 that was previously identified as a nuclear localization sequence (NLS) containing nucleolar‐targeting signals . As shown in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It appears intriguing that ING4, which is generally viewed as a transcription-regulatory factor interacting with methylated histones (in particular H3K4me3) [ 48 ] and DNA [ 49 ] has major cytoplasmic functions as well. However, ING4 reportedly acts on NF-κB as an E3 ubiquitin ligase [ 36 ], and at least a fraction of ING4 is located in the cytoplasm [ 24 ], supporting the possibility that it exerts important extranuclear functions.…”
Section: Resultsmentioning
confidence: 99%